Implementation of a Novel Control Technique in Landsman Converter Using Bumble Bee Optimization - A. Rahiman, Riyaz; C. John Wiselin, M (International Journal of Engineering and Technology, 2018)
This paper focuses on a solar PV array based BLDC motor employing Landsman converter under partial shading condition (PSC). A converter acts as an interface between the SPV array under PSC and Voltage Source Inverter (VSI) feeding the Brushless DC (BLDC) motor. BLDC motor incorporating the merits of higher efficiency, high reliability, high ruggedness, easy-to-drive, capability to operate successfully at low voltage and excellent performance over a wide range of speed. The speed control of BLDC motor by variable DC-link voltage. This eliminates the additional phase current sensing, DC-link voltage sensing, additional control and associated circuitry. The proposed system includes simplicity control, compactness, and soft starting of the BLDC motor. The operation of Landsman converter in CCM results reduced stress on devices.Â To optimize the operating point of the SPV array in order to get maximum possible power output by means of the better maximum power point tracking (MPPT) technique. The technique is Bumble Bee Mating Optimization (BBMO) based MPPT. The novel technique is compared to the conventional techniques. The simulated results are executed in MATLAB/SIMULINK.